PENGARUH MUATAN LEBIH BEBAN GANDAR KENDARAAN BERAT ANGKUTAN BARANG TERHADAP PENINGKATAN OKSIDA KARBON - Wahyudi, Wahid; Taufik Mulyono, Agus; Santosa, Wimpy (Jurnal Transportasi, 2013)
At present, the influence of overloaded freight vehicles only associated with damage to the road structure and road congestion or services. Overloading is not considering the effect of the increase of carbon oxides. Increased carbon oxides on overloaded vehicles occur due to increased fuel consumption and heavy vehicle engine work. This study aimed to obtain the relationship between axle load overloading offenses with increased carbon oxides carried by freight vehicles in the Province of East Java. The method used is direct measurement in several weigh in East Java Province. The excess weights of freight vehicles were measured and then carbon oxide emission tests were performed to measure the carbon monoxide and carbon dioxide emissions. The results indicate that there is a linear relationship between the excess loads carried by freight vehicles with increased carbon oxides. Carbon dioxide increased significantly in line with overloaded heavy freight vehicles. Therefore, the policy to implement sanctions, such as fines for overloaded freight vehicles should include cost components due to increased emissions of carbon oxides, such as reduction cost and community loss affected by these pollutants.Keywords: heavy vehicle, overload, freight vehicle, carbon oxides